Demand for Taenia solium Cysticercosis Vaccine: Lessons and Insights From the Pig Production and Trading Nodes of the Uganda Pig Value Chain - Ouma, Emily; Dione, Michel; Mtimet, Nadhem; Lule, Peter; Colston, Angie; Adediran, Samuel; Grace, Delia (Frontiers in Veterinary Science, 2021)
Taenia solium cysticercosis disease remains a key challenge to the pig sector in low- and middle-income countries in sub-Saharan Africa, Latin America and South East Asia, resulting in both economic losses and public health impacts. The World Health Organization has ranked it first on the global scale of foodborne parasites. A One Health approach has been recommended for reduction of infection pressure and eradication in the longer term. A new vaccine TSOL18 (Cysvax™), applied in combination with oxfendazole (Paranthic 10%™), a dewormer drug has been developed and field tested for the control of T. solium cysticercosis, with high potential to break the disease cycle. It is however unclear whether the products can be marketed through a market driven approach, and if smallholder pig farmers would be willing to take up and pay for the vaccine - oxfendazole combination. A choice experiment methodology was used to assess the potential demand and willingness to pay for the vaccine – oxfendazole combination by Ugandan smallholder pig farmers, and demand for vaccinated pigs by pig traders. The results showed that farmers highly valued quality assurance attributes and were not keen on the vaccine if there were no associated returns in the form of premium price for vaccinated pigs during sales. They were willing to pay US$ 2.31 for the vaccine if it resulted in a premium price for vaccinated pigs. Furthermore, they preferred an accompanying vaccine viability detector as part of its quality assurance. The pig traders on the other hand preferred high carcass weight of pigs, potentially achieved by using oxfendazole. The results show that unless the pig market systems pay a premium price for vaccinated pigs, and quality assurance systems guarantee quality vaccine, uptake of the TSOL18 vaccine and oxfendazole by farmers through market mechanisms may be unsuccessful. The current pig marketing system does not reward food safety, the focus is mainly on carcass weight. Alternative delivery mechanisms for the vaccine through a mix of private - public investments needs to be explored, as the benefits of vaccinated pigs are societal and include reduction and elimination of neurocysticercosis in the long run.